Südwestasien. Erstellung einer Referenzkollektion für makro- und mikroskopische Abnutzungsspuren an Reibsteinen Vorderasiens. Die Arbeiten des Jahres 2020 - Dietrich, Laura (e-Forschungsberichte des DAI, 2021)
The project focuses on macro- and microscopical traceology to produce an image database as a reference collection for functional analysis of grinding and pounding tools from southwestern Asia. Wear patterns are produced through long-term experiments with replicas, which are compared to original artifacts from several excavation projects. Another aim is to develop quantification methods for wear, which would offer insights into the duration of use of grinding gear.